The Integration Of Revelation And Reason In The Qur'an A Thematic Exegetical Study - ليلى معاش (مجلة الاجتهاد للدراسات القانونية والاقتصادية)
This study explores the integration of revelation and reason within the Holy Quran, a vital intellectual challenge in Muslim history and contemporary discourse. The Quran, as the primary cognitive framework for Muslims, guides the examination of the relationship between revelation and reason. Utilizing inductive tracing of terms, analytical verse analysis, and deductive interpretations, the research clarifies how revelation and reason coexist harmoniously, influenced by the principles of monotheism. This balance is crucial for understanding the Quranic text and contemplating the universe, providing a dual reading that enriches knowledge. The findings emphasize that the Quran remains an essential reference for addressing intellectual and cognitive challenges, underscoring the integration of revelation and reason as foundational to obtaining true knowledge and resolving the perceived conflict between these two domains